Crossbreeding cattle in beef production programmes in Kenya. II. Comparison of purebred Boran and Boran crossed with the Red Poll and Santa Gertrudis breeds - Trail, J.C.M.; Gregory, K.E.; Durkin, J.W.; Sandford, J. (Springer, 1984)
Compares two series of breed groups of cows for maternal traits from a three-year study in Kenya to identify breed crosses that are superior to the Boran purebreds; considers age at first calving, calving interval, calf weight at weaning, cow weight at weaning, calf mortality to weaning and cow proudctivity indices.